No Benefit in Neurologic Outcomes of Survivors of Out-of-Hospital Cardiac Arrest with Mechanical Compression Device. (4th May 2018) - Newberry, Ryan; Redman, Ted; Ross, Elliot; Ely, Rachel; Saidler, Clayton; Arana, Allyson; Wampler, David; Miramontes, David
Abstract: Introduction : Out-of-hospital cardiac arrest (OHCA) is a major cause of death and morbidity in the United States. Quality cardiopulmonary resuscitation (CPR) has proven to be a key factor in improving survival. The aim of our study was to investigate the outcomes of OHCA when mechanical CPR (LUCAS 2 Chest Compression System™) was utilized compared to conventional CPR. Although controlled trials have not demonstrated a survival benefit to the routine use of mechanical CPR devices, there continues to be an interest for their use in OHCA.Methods : We conducted a retrospective observational study of OHCA comparing the outcomes of mechanical and manual chest compressions in a fire department based EMS system serving a population of 1.4 million residents. Mechanical CPR devices were geographically distributed on 11 of 33 paramedic ambulances. Data were collected over a 36-month period and outcomes were dichotomized based on utilization of mechanical CPR. The primary outcome measure was survival to hospital discharge with a cerebral performance category (CPC) score of 1 or 2.Results : This series had 3, 469 OHCA reports, of which 2, 999 had outcome data and met the inclusion criteria. Of these 2, 236 received only manual CPR and 763 utilized a mechanical CPR device during the resuscitation. Return of spontaneous circulation (ROSC) was attained in 44% (334/763) of the mechanical CPR resuscitations and in 46% (1, 020/2, 236) of the standard manual CPR resuscitations (p = 0.32). Survival to hospital discharge was observed in 7% (52/763) of the mechanical CPR resuscitations and 9% (191/2, 236) of the manual CPR group (p = 0.13). Discharge with a CPC score of 1 or 2 was observed in 4% (29/763) of the mechanical CPR resuscitation group and 6% (129/2, 236) of the manual CPR group (p = 0.036).Conclusions : In our study, use of the mechanical CPR device was associated with a poor neurologic outcome at hospital discharge. However, this difference was no longer evident after logistic regression adjusting for confounding variables. Resuscitation management following institution of mechanical CPR, specifically medication and airway management, may account for the poor outcome reported. Further investigation of resuscitation management when a mechanical CPR device is utilized is necessary to optimize survival benefit.